Acute Q fever in patients with an influenza-like illness in regional New South Wales, Australia - Rodrigo, Chaturaka; Walker, Gregory; Sevendal, Andrea T. K.; Nguyen, Chelsea; Stelzer-Braid, Sacha; Rawlinson, William; Graves, Stephen; Gidding, Heather F.; Stenos, John; Lloyd, Andrew R. (PLOS Neglected Tropical Diseases, 2024)
Author summary Q fever is a highly contagious infection presenting as an influenza-like illness or less commonly as acute hepatitis. Literature shows that there may be diagnostic delays in recognizing Q fever by primary care physicians if they are unfamiliar with the infection. We tested residual serum samples stored at NSW Health Pathology between 2016–2023 for Q fever, if that sample originated from a rural postcode in NSW and had been tested previously for an organism causing influenza like illnesses, but not Q fever. After testing 542 eligible samples only one case of missed acute Q fever was found. In the same period, from a similar population the same diagnostic laboratory received 731 requests for Q fever testing from which 70 were positive. Therefore, In this study the number of missed acute Q fever cases were clinically insignificant.